Proresolution Therapy for the Treatment of Delayed Healing of Diabetic Wounds - Tang, Yunan; Zhang, Michael J.; Hellmann, Jason; Kosuri, Madhavi; Bhatnagar, Aruni; Spite, Matthew (Diabetes (New York, N.Y.), 2013)
Obesity and type 2 diabetes are emerging global epidemics associated with chronic, low-grade inflammation. A characteristic feature of type 2 diabetes is delayed wound healing, which increases the risk of recurrent infections, tissue necrosis, and limb amputation. In health, inflammation is actively resolved by endogenous mediators, such as the resolvins. D-series resolvins are generated from docosahexaenoic acid (DHA) and promote macrophage-mediated clearance of microbes and apoptotic cells. However, it is not clear how type 2 diabetes affects the resolution of inflammation. Here, we report that resolution of acute peritonitis is delayed in obese diabetic (db/db) mice. Altered resolution was associated with decreased apoptotic cell and Fc receptor–mediated macrophage clearance. Treatment with resolvin D1 (RvD1) enhanced resolution of peritonitis, decreased accumulation of apoptotic thymocytes in diabetic mice, and stimulated diabetic macrophage phagocytosis. Conversion of DHA to monohydroxydocosanoids, markers of resolvin biosynthesis, was attenuated in diabetic wounds, and local application of RvD1 accelerated wound closure and decreased accumulation of apoptotic cells and macrophages in the wounds. These findings support the notion that diabetes impairs resolution of wound healing and demonstrate that stimulating resolution with proresolving lipid mediators could be a novel approach to treating chronic, nonhealing wounds in patients with diabetes.